The impact of policy perception on technology transfer from boundary-spanning perspective-empirical evidence from Chinese technological enterprises - Zhang, Kaiyun; Wang, Qingjin; Wang, Xueling; Zhang, Fengying (Frontiers in Psychology, 2022)
Technology transfer is an essential source of technological innovation for enterprises, which is conducive to the market transformation of patent achievements and the commercial application of new technologies. Building upon social capital theory, all data analyses were performed using SPSS 22.0 and Amos software with the multiple linear regression method. The study explores the mechanism of policy perception to obtain the technical resources needed for enterprise development through boundary-spanning behaviour, with a moderating effect of inter-organizational trust and technological potential gap. The study uses survey data from 125 enterprise teams of 42 technology-based enterprises in China. The results show that policy perceived usefulness and usability significantly promote technology transfer performance and boundary-spanning behavior plays a mediating role between them. Speaking of the influencing factors of technology transfer, technological potential gap significantly moderates the relationship between boundary-spanning and technology transfer performance. In contrast, inter-organizational trust positively moderates the relationship between boundary-spanning and technology transfer performance. The research provides theoretical reference and guidance for enterprises on using policy perception better to improve technology transfer performance in the institutional environment. It also helps inspire enterprises to better deal with the cooperative relationship between relevant stakeholders and achieve win-win cooperation.